TRANSFORMATION OF TEACHERS' PEDAGOGICAL COMPETENCIES IN LEARNING PANCASILA THROUGH ACADEMIC SUPERVISION IN ELEMENTARY SCHOOLS (Pena Cendekia Insani, 2026)
The principal’s academic supervision plays an important role in improving teachers’ pedagogical competence, particularly in Pancasila learning at the elementary school level. This study aims to describe the transformation of teachers’ pedagogical competence after the implementation of academic supervision by the principal. This research employed a descriptive qualitative approach at SD Negeri 3 Parangharjo, SD Negeri 1 Pujiharjo, and SD Negeri Wonoharjo, Wonogiri Regency. Data were collected through interviews, observations, and documentation, and were analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings show that the most prominent development occurred in teachers’ ability to design more systematic learning and implement more active, participatory, and student-centered learning. Teachers also began to use discussion, question-and-answer activities, group work, and contextual learning methods to connect Pancasila values with students’ real-life experiences. In addition, academic supervision encouraged teachers to conduct learning evaluation and reflection in a more focused manner, although the aspects of attitude assessment and reflective follow-up still require further strengthening. This study concludes that academic supervision functions not merely as administrative monitoring, but as a humanistic, collaborative, and sustainable professional development process to improve the quality of Pancasila learning in elementary schools.